Ageing and physical match performance in English Premier League soccer referees - Weston, M.; Castagna, C.; Impellizzeri, F. M.; Rampinini, E.; Breivik, S. (Journal of Science and Medicine in Sport, 2010)
Soccer referees are required to keep up with play at all times despite occupying an age bracket of on average 10-15 years older than their playing counterparts. Therefore, the aim of the present study was to examine the effect of age upon the physical match performances and match physiological loads of elite-level soccer referees. Match analysis data was collected (Prozone®, Leeds, UK) from 22 professional soccer referees (age range 31-48 years) on FA Premier League matches over four consecutive seasons (778 observations). Physical match performance categories were total-distance covered (TD); high intensity running distance (speed >5.5 m/s, HIR); sprint count (>7.0m/s, SC); top sprinting speed (TS); average distance from the ball (DB) and average distance from fouls (DF). Significant age effects were found for TD (r=-0.52, p<0.001), HIR (r=-0.53, p<0.001) and SC (r=-0.53, p<0.001). No age effect was found for DB and DF (p>0.05). Despite covering less TD, HIR and performing fewer sprints the older referees (43-48 years) were able to maintain an average distance from fouls that was comparable to that recorded by the young (31-36 years) referees. Therefore, the reduced physical match performances associated with increasing referee age did not appear to impact upon the older referees' ability to keep up with play. In light of these findings, refereeing governing bodies may wish to review their age-based retirement guidelines.